2011
DOI: 10.1002/jnr.22684
|View full text |Cite
|
Sign up to set email alerts
|

Slit‐Robo signals regulate pioneer axon pathfinding of the tract of the postoptic commissure in the mammalian forebrain

Abstract: During early vertebrate forebrain development, pioneer axons establish a symmetrical scaffold descending longitudinally through the rostral forebrain, thus forming the tract of the postoptic commissure (TPOC). In mouse embryos, this tract begins to appear at embryonic day 9.5 (E9.5) as a bundle of axons tightly constrained at a specific dorsoventral level. We have characterized the participation of the Slit chemorepellants and their Robo receptors in the control of TPOC axon projection. In E9.5–E11.5 mouse emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Robo2 and Slit1 were expressed in the mouse developing hypothalamus from E10.5 and were required to maintain proper balance between primary and intermediate neuronal progenitors [27]. This function was probably conserved in the chick.…”
Section: Discussionmentioning
confidence: 99%
“…Robo2 and Slit1 were expressed in the mouse developing hypothalamus from E10.5 and were required to maintain proper balance between primary and intermediate neuronal progenitors [27]. This function was probably conserved in the chick.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our observations, it has been shown that FGFRs regulate axon guidance cues such as slit and semaphorin3A to control axonal pathfinding 46,49 . Slit-Robo signals regulate the pathfinding of multiple axonal pathways, including corticofugal, thalamocortical, and callosal connection [68][69][70][71] . Frizzled-3, one of the members in Wnt-Frizzled pathway, is required for the development of multiple axon tracts including anterior commissure, corticofugal axons, thalamocortical axons, and corpus callosum in the mouse CNS [72][73][74][75] .…”
Section: Fgfr3 Gof In Nex-lineage Neurons Leads Miswiring Of Several mentioning
confidence: 99%
“…S4). Robo-Slit signaling regulates the guidance of longitudinally projecting axons in the developing mouse brain stem (Dugan et al, 2011;Farmer et al, 2008;Mastick et al, 2010), forebrain (Devine and Key, 2008;Ricano-Cornejo et al, 2011) and spinal cord (Reeber et al, 2008 (Brose et al, 1999;Kadison et al, 2006;Yuan et al, 1999) might play a key role in constraining the orientation of longitudinally projecting SACMN axons as Slit1 and Slit2 position retinal ganglion cell axons at the optic chiasm (Plump et al, 2002).…”
Section: Nkx29 Regulates Robo2 Expressionmentioning
confidence: 99%